Dampak Penyebaran Covid-19 terhadap Dunia Pendidikan dan Sanitasi Di Indonesia - Angelica, Felicia; Tan, Kendry; Lauw, Alvin; Rosalya, Wini; Sheerleen, Sheerleen (Ridwan Institute, 2021)
This article is intended to provide further explanation regarding the impact that Covid-19 has towards the education and sanitation system around the world. Sustainable Development Goals is a program to globally improve the people’s living quality. Indonesia, which has signed the Sustainable Development Goals treaty, has participated in actualizing the goals and objectives of Sustainable Development Goals. On the other side, COVID-19 is declared as a pandemic. It has given huge impact on the progress to achieve Sustainable Development Goals. In this article, the team of authors will be mainly discussing about the fourth and sixth goals, which are quality education and clean water and sanitation.. This study aims to provide solutions for problems in achieving the Sustainable Development Goals due to the occurrence of Covid-19. The author processed and analyses the data by descriptive approach. The result of this study is expected to show the impact of Covid-19 pandemic on the Sustainable Development Goals agenda. And with that, this article will be discussing about solutions to the problem that had risen from the Covid-19 pandemic.